Utility of decellularised urinary bladder extracellular matrix in full mucosalisation of a post-oncological maxillectomy defect. Issue 10 (December 2020) - Graillon, N.; Le, A.D.; Chang, B.M.; Shanti, R.M.
Abstract: This report highlights the utility of MatriStem Surgical Matrix Thick UBM™ (rebranded as Gentrix® ACell, Inc), a decellularised urinary bladder extracellular matrix in the reconstruction of a post-oncological maxillectomy defect. In utilising this biological construct to serve as a biological dressing, our patient underwent complete mucosalisation of his surgical site without the development of an oroantral fistula and with adequate maxillary vestibule to allow for definitive oral rehabilitation with a removable partial denture.